Experimental and numerical optimization of direct-contact liquid film cooling in high concentration photovoltaic system. (15th December 2017) - Wang, Yiping; Zhou, Liqun; Kang, Xue; Huang, Qunwu; Shi, Xusheng; Wang, Chen
Highlights: The direct-contact liquid film cooling is experimentally and numerically investigated. The temperature of simulated dense-array solar cells is well controlled and the temperature distribution is uniform. The flow characteristic of liquid film and heat transfer performance is analyzed. The effects of various inlet parameters are obtained and the best optimizing combination of inlet parameters is achieved. The calculated cooling capacity is so prominent that the heat transfer coefficient is above 5000 W/m 2 ·K. Abstract: Thermal management is a critical issue for normal operation of dense-array solar cells in high concentration photovoltaic system. A cooling method of direct-contact liquid film was experimentally and numerically investigated. In the experiments, deionized water was adopted as coolant and an electric heating plate was optimal designed to simulate dense-array solar cells. A two-dimension model was derived to present the temperature distribution on the surface of the simulated solar cells and flow characteristic of liquid film. The effect of various inlet parameters such as water temperature, inlet width and velocity had been numerical studied. The experiment results suggest that the surface temperature is well controlled under 120 °C at corresponding conditions, with concentration ratios ranging from 300 to 500X. The numerical results show that inlet width has a crucial effect on the liquid film thickness. The subcooled boiling state is a necessary condition to ensure cooling effect. High water inlet temperature is preferable for better heat transfer performance and temperature uniformity. The best optimizing inlet velocity, width and temperature are 1.06 m/s, 0.75 mm and 75 °C, respectively.